ANALISIS USAHATANI BERKELANJUTAN PADA RUMAHTANGGA TANI DI DAERAH LAHAN PASANG SURUT KALIMANTAN TENGAH - Wardie, Jhon; Hartono, Slamet; Darwanto, Dwidjono Hadi; Irham, . (Jurnal AGRISEP, 2011)
This research is aimed to analyse level income and level farm sustainability at farm household in tidal swamps area Central Kalimantan. This research   location, i.e.,  Kapuas regency is selected purposively and 100  samples are  sampled purposively on the basis of  two difference farming locations  of tidal swamps area that managed by local farm households and non local farm households.  Level farm household income then analysed with tabulate from whole activity. Analysis to indicate the difference level of  farm household income between local and  non local farm household use  t-test. . The  farm sustainability is  analysed with indicator skoring farm sustainability. The research showed that there is no significant difference between local and non local farm household income statistically eventhough local farm household income is higher than that of non local. The research also revealed that level farm sustainability of non local farm household is categorized as high sustainable, while  local farm household is categorized into moderate. Result from t-test indicates  a significant difference of  sustainability index value between two farm households. . Furthermore, Farm households have right motivation  and apply sustainable agriculture principles which is emphasized to take care of environmental continuity of natural resources without neglecting in increasing of productivity  and income. In terms of  external  and internal input usage, non local farm household behavior and attitudes is better than local farm household.Keywords: tidal swampsarea, farm household, sustainable farming, external input